2011
DOI: 10.1186/1471-2458-11-93
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood and factors that influence outdoor recreational physical activity from a gender perspective

Abstract: BackgroundA physically active life promotes both physical and mental health, increasing well-being and quality of life. Physical activity (PA) performed outdoors has been found to be particularly good for promoting well-being. However, participation in PA can change during the course of a lifetime. Parenthood has been found to be a life event associated with decreased PA, especially among women, although studies in the field are sparse. The aim of this study was to investigate participation in outdoor recreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
2
21
0
2
Order By: Relevance
“…Após a leitura do título e dos resumos foram selecionados 54 estudos para leitura integral, sendo 11 estudos [55][56][57][58][59][60][61][62][63][64][65] descartados após a leitura, restando assim 43 artigos analisados integralmente e inclusos nesta revisão.. Os principais motivos para a exclusão de artigos foi por se tratar de estudos com o objetivo de estabelecer associações entre as condições socioeconômicas com síndromes e/ou doenças, estudos qualitativos e de revisão. O fluxograma do processo de seleção dos artigos ou estudos foi representado na Figura 1.…”
Section: Resultsunclassified
“…Após a leitura do título e dos resumos foram selecionados 54 estudos para leitura integral, sendo 11 estudos [55][56][57][58][59][60][61][62][63][64][65] descartados após a leitura, restando assim 43 artigos analisados integralmente e inclusos nesta revisão.. Os principais motivos para a exclusão de artigos foi por se tratar de estudos com o objetivo de estabelecer associações entre as condições socioeconômicas com síndromes e/ou doenças, estudos qualitativos e de revisão. O fluxograma do processo de seleção dos artigos ou estudos foi representado na Figura 1.…”
Section: Resultsunclassified
“…In a study by Klompstra et al (13) one-third of the subjects had low levels of activity, and this confirms our research findings. Sjogren's study (14) also on physical activity showed that most persons were inactive.…”
Section: Discussionmentioning
confidence: 96%
“…The majority of studies of gender roles and norms and their impact on specific health conditions have been generally limited to reproductive health, domestic violence and mental health (Boileau et al, 2008;Collins, von Unger, & Armbrister, 2008;Ghanotakis, Peacock, & Wilcher, 2012;Kerrigan, Andrrinopoulos, Chung, Glass, & Ellen, 2008;Mantell et al, 2009;Paek, Lee, Salmon, & Witte, 2008;Phillips & Phillips, 2010;Wagner, Yates, & Walcott, 2012;Zuo et al, 2012). Less is known about the impact of gender on health behaviors, specifically in the area of obesity and lifestyle factors that influence healthy weight, such as diet (Costanzo, Musante, Friedman, Kern, & Tomlinson, 1999;Fagerli & Wandel, 1999;Frank et al, 2009;Gavin, Fox, & Grandy, 2011;Gray, Cinciripini, & Cinciripini, 1995) and physical activity (Butt, Weinberg, Breckon, & Claytor, 2011;Frank et al, 2009;Gavin et al, 2011;Langer et al, 2009;McLaren, Godley, & MacNairn, 2009;Sjogren, Hansson, & Stjernberg, 2011;Sjogren & Stjernberg, 2010;Slater & Tiggemann, 2011;Spence et al, 2010), although interest in these topics has increased in recent years.…”
Section: Sex Gender and Healthmentioning
confidence: 99%